TESTIMONY, ANALYSIS, AND VISUAL STRATEGY OF THE 1968 STUDENTS’ MOVEMENT: RAUL ALVAREZ GARIN’S AND GILBERTO GUEVARA NIEBLA’S CASES. (Tzintzun, Revista de Estudios Históricos, 2016)
After 40 years, the 1968 students’ movement has generated great historiographicreflection which includes testimonies, academic and political analysis, movies, andother cultural products. One of the most productive works s has been the publishingof chronics, testimony and analysis made by the same leaders of the movement.These works have been enriched by the publishing of two leaders’ testimonies: RaúlÁlvarez Garín and Gilberto Guevara Niebla. Each one of them has given his versionof the facts. These versions have generated coherent and complex visions whichincorporate their viewpoint to a global reading of the facts. Differences and nuanceare highlighted in this paper. And the most important, a first analysis on how thetwo leaders designed their visual strategy to support their reflections is developed.
Keywords: Students’ movement; 1968 Mexico; Students’ movement iconography; repression; political crime